Staying fit: a must to be a successful Neurosurgeon - Thapa, Amit (Nepal Journal of Neuroscience, 2021)
When I decided to be a neurosurgeon, I was told that my professional life is going to be very short. At the start you would begin late as it takes long to be a competent one and later due to stress of life and work, soon you would feel either exhausted or due to physical issues would soon stop operating. Well this doomsday prediction for a career neurosurgeon may discourage new enthusiasts, the seasoned practitioner however knows what it takes to continue your career graph go up for long. Neurosurgeons need a blend of skills and personal qualities like a high degree of manual dexterity, good hand-eye co-ordination, excellent vision and visuo-spatial awareness, good organisational ability and effective decision-making skills. To achieve this professional requirement and to keep going strong, we need a healthy body and a problem-solving mind.